2017
DOI: 10.1038/s41598-017-07204-w
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase reverse transcriptase promotes chemoresistance by suppressing cisplatin-dependent apoptosis in osteosarcoma cells

Abstract: Cisplatin is one of the most efficacious antimitotic drugs used in the treatment of a range of malignant tumors. However, treatment failures are common due to the development of chemoresistance. In addition to its telomere maintenance function, telomerase plays a pro-survival role, inducing decreased apoptosis and increased resistance against DNA damage. Elucidation of the molecular mechanisms underlying this effect is critical to improve treatment outcomes. Previously, our group showed higher telomerase rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 40 publications
0
26
1
Order By: Relevance
“…To assess the effect of the combinatorial treatment on the immortalization of the PTES cells, the mRNA expression of the catalytic subunit hTERT was examined in the present study. Previous studies revealed that telomerase expression was increased in osteosarcoma cisplatin-resistant cells, thus leading to the suppression of cisplatin-induced apoptosis (50). However, hTERT expression was significantly decreased in the PTES cells in the present study.…”
Section: Discussioncontrasting
confidence: 60%
“…To assess the effect of the combinatorial treatment on the immortalization of the PTES cells, the mRNA expression of the catalytic subunit hTERT was examined in the present study. Previous studies revealed that telomerase expression was increased in osteosarcoma cisplatin-resistant cells, thus leading to the suppression of cisplatin-induced apoptosis (50). However, hTERT expression was significantly decreased in the PTES cells in the present study.…”
Section: Discussioncontrasting
confidence: 60%
“…The data demonstrated that miR-192-5p mimics reduced chemo-resistance of osteosarcoma cells to cisplatin. And it had been reported that the cisplatin drug was presented the chemio-sensitivity in osteosarcoma cells ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…4 The reasons for chemotherapy resistance in cancer treatment are multifaceted, and include the increased expression of ABC transporters (including MDR1, P-gp, MRP, and BCRP) and changes in cell membrane permeability that leads to drug efflux; impairment of DNA damage repair mechanisms; autophagymediated drug resistance; changes in tumor cell microenvironment; and mutations in drug targets. [5][6][7] Among these mechanisms, autophagy-mediated chemotherapy resistance has gained increasing attention. 5,6 Autophagy, a conservative life process in all eukaryotic cells, plays an important role in maintaining a stable intracellular environment and protein balance.…”
Section: Introductionmentioning
confidence: 99%